228 PD-1-TARGETED T-CELL CHECKPOINT INHIBITORS-RELATED MYOCARDITIS COMPLICATED BY COMPLETE ATRIOVENTRICULAR BLOCK: A CASE SERIES OF SUCCESSFUL MANAGEMENT. (15th December 2022) - Collini, Valentino; Imazio, Massimo; De Biasio, Marzia; Lepre, Veronica; Burelli, Massimo; Taurian, Marco; Pellin, Lisa; Sinagra, Gianfranco
Abstract: Background: Immune checkpoint inhibitors (ICI) have revolutionized the clinical management of a broad spectrum of solid and hematopoietic malignancies over the past decade. ICI are associated with several Immune-related Adverse Events, among which myocarditis and atrioventricular blocks are uncommon but potentially fatal toxicities. Material and Methods: We describe two patients undergoing treatment with PD-1 checkpoint inhibitors for metastatic cancers who developed myositis and myocarditis complicated by complete atrioventricular block (CAVB). The first patient had a history of metastatic sarcomatoid urothelial carcinoma treated with Pembrolizumab. After two cycles, he developed eyelid ptosis and was hospitalized for syncopal episodes due to CAVB associated with ICI myocarditis. The second patient had a history of metastatic melanoma and was hospitalized for myocarditis and myositis after the second infusion of Nivolumab. Results: In the first case, high-dose corticosteroid therapy was promptly initiated, with subsequent rapid recovery of sinus rhythm and rapid resolution of symptoms. The second patient, despite high-dose corticosteroid therapy, developed CAVB requiring implantation of a definitive PM. After initiation of mycophenolate mofetil and intravenous immunoglobulin therapy, gradual recovery was observed. Both patients had normal left ventricular function with no wall motion abnormalities. However, speckle tracking echocardiography revealed a normal global longitudinal left ventricular strain (GLS) of -19.8% in patient 1 and a depressed GLS of -14.7% in patient 2, consistent with the different evolution of the two myocarditis. Conclusions: We recommend a high degree of caution and awareness to all physicians when treating immunotherapy patients. Myocarditis is a relatively rare but potentially fatal event due to its early onset, non-specific clinical presentation and fulminant progression. GLS may be useful in detecting myocardial damage in these patients. Discontinuation of ICI, cardiac pacing, treatment with high-dose corticosteroids and immunosuppressive agents may improve the outcome.